Sero-epidemiology of Japanese encephalitis virus among livestock, avian and companion animals in selected states of Malaysia - Karunanithi, Kiven Kumar (2017)
Japanese encephalitis (JE) is vector-borne disease causes encephalitis in human and horse as well as reproductive failure in sows. Pigs, bats, wild boar, and ardeidae birds play an important role as a main vertebrate amplifier of JEV. In Malaysia the disease is endemic in east Malaysia, Sarawak and epidemic in Peninsular Malaysia. The encephalitis cases were observed among human and animals reported in earlier 1950s. However, they are no data regarding seroprevalence pattern among livestock (buffaloes, pigs, cattle), avian (captivity water birds, poultry and migratory birds) and companion animals (cats, dogs). At the same time, risk factors associated with JEV seroprevalence in high risk areas in Malaysia are not documented. In this study, the objectives are to determine JEV seroprevalence rate, risk factors associated with JEV seroprevalence and determination of JEV genotype circulating among livestock (buffaloes, pigs, cattle), avian (water captivity birds, poultry and migratory birds) and companion animals (cats, dogs) were documented. Total of 461 serum samples were collected from dogs, cats, captivity water birds, village chickens, domestic pigs, buffaloes and cattle in selective states of Perak, Selangor and Sabah and screened for evidence of JEV antibodies by using a double sandwich IgG ELISA kits (DAS-ELISA). The risk factors associated with JEV seroprevalence of the animals were analysed by using IBM SPSS 22 which included Chi-square (χ2 test is not appropriate if one of expected cell value is less than 5, Fisher’s exact test was used at α = 0.05) and multiple logistic regression. A total of 13 survey criteria which include gender (male vs female), health status (healthy vs sick), age (young vs adult), breeding types (local, vs import), ownership of animal (own, shelter or none) and source of animals (same area, same district, same state vs epidemic areas) were collected. At the same time, environmental factors of sampling areas including presence of stagnant water (yes or no), paddy cultivation (yes or no), presence of ardeid birds (yes or no), locality (urban vs rural) and presence of mosquitos (yes or no). In the molecular assay, total of 791 samples of plasma, serum, and buffy coat from livestock (buffaloes, pigs, cattle), companion animals (cats, dogs) and avian (water captivity birds, poultry and migratory birds) were subjected to one step RT-PCR to detect the JEV by targeting the conserved region of NS3 of the JEV. In seroprevalence study among the animals studied, dogs show the highest seropositive rate of 80% (36/45; 95%CI: ±11.69) followed by pigs with 44.4% (40/90; 95% CI: ±1.715), buffaloes with 33.3% (15/45; 95% CI: ± 6.661), cattle with 32.2% (29/90; 95% CI: ±1.058), avian 28.9% (13/45; 95% CI: ±5.757), and cats with 14.4% (13/90; 95% CI: ±7.38). This study reveals that the risk factors associated with JEV seroprevalence are varied among different species of animals. The risk factors involved in different species of animals can be either singly or more than one. In additional to that, geographical factors may influence on the seropositivity of animals to JEV. In dogs, significant risk factor associated with JEV seroprevalence is the source of dog. In cats, significant risk factors associated with JEV seroprevalence are the age, locality, breeding types, and source of cats. In cattle, significant risk factors associated with JEV seroprevalence are gender, healthy status, breeding types and source of cattle. In pigs, significant risk factors associated with JEV seroprevalence are age and ownership of pigs. In buffaloes, significant risk factors associated with JEV seroprevalence are the source of buffalo and breeding types. In avian, significant risk factors associated with JEV seroprevalence are age and the breeding types. In this study, the high JEV seroprevalence in dogs observed is believed due to the preference and selective feeding pattern of Culex spp. in dogs compared to cats or human, thus making the dogs more prone to infection. JEV seroprevalence in pigs in this study are lower than reported previously probably due to the location of the subject matter in a non-paddy cultivation areas. This study also observed that JEV seroprevalence rate in buffaloes and cattle are low and support previous finding of this species play minimum role in JEV transmission cycles. The low viremia following JEV infection is too low of viral load to infect vector. Low JEV seroprevalence observed in chickens in this study is rather unexpected as avian was sampled in high risks areas with paddy plantation, water bodies and mosquitoes breeding sites. This finding may be further support by the lack of pig farming in this area, as the residents are engaged in fishing activities besides paddy cultivation. In this study, JEV antigen was unable to be detected in all the samples collected from various species of animals. Preliminary findings show that, all the animals were negative for JEV antigen. This could be due to the presence of antibodies of JEV naturalised the antigen. Apart from that, the sero-complex characteristics of flaviviruses make the antigen-antibodies cross-react with each other members. This makes the antigen being neutralised and unable to be detected in blood of the host. Samples collected during acute stage of JEV infection in animals have high chances of virus being isolated. In addition to that, the oronasal fluid is preeminent for isolation and detection of JEV antigen compared to serum, cerebrum spinal fluid, plasma and buffy coat.